Factors associated with clinical outcomes among children with delayed diagnosis of critical congenital heart disease: A cross-sectional study - Fachrozi, Muhammad R.; Adriansyah, Rizky; Pratita, Winra; Wahyuni, Arlinda S.; Tobing, Tina CL.; Trisnawati, Yunnie (Narra Sains Indonesia, 2025)
Delayed detection of critical congenital heart disease (CHD) is associated with increased morbidity and mortality. Currently, there is a paucity of data on children with critical CHD in Indonesia. The aim of this study was to investigate the factors contributing to delayed diagnosis of critical CHD and its association with clinical outcomes such as mortality, heart failure, intensive care unit (ICU) admission, and ventilator use. A cross-sectional study was conducted using medical records from Haji Adam Malik Medan General Hospital. The study included all children aged 0 to 18 years diagnosed with critical CHD. The statistical analysis was performed by utilizing SPSS version 25.0. A total of 59 subjects were analyzed. The findings revealed a significant relationship between factors such as age, sex, respiratory tract infections, type of CHD, surgical interventions, and underlying syndromic abnormalities with various clinical outcomes. Delayed diagnosis of critical CHD was associated with increased mortality, heart failure, ICU admission, and ventilator use, with these outcomes influenced by the aforementioned factors.